2016
DOI: 10.18632/oncotarget.8441
|View full text |Cite
|
Sign up to set email alerts
|

Aberrantly activated Gli2-KIF20A axis is crucial for growth of hepatocellular carcinoma and predicts poor prognosis

Abstract: Glioma-associated oncogene 2 (Gli2), a primary transcriptional regulator of Hedgehog (Hh) signaling, is essential for hepatocellular carcinoma (HCC) growth and survival. However, the underlying molecular mechanism and crucial downstream targets of Gli2 in human HCC are not fully understood. Here, we report the identification of kinesin family member 20A (KIF20A) as a novel downstream target of Gli2, which is important for HCC proliferation and tumor growth. Inhibition of Hh signaling leads to a remarkable decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 42 publications
7
79
0
Order By: Relevance
“…KIF20A is a member of the KIF family, which has been reported to be upregulated in pancreatic cancer,29 breast cancer,14 and hepatocellular cancer 30. In the current study, we investigated the expression of KIF20A protein in gliomas using IHC and found that the expression of KIF20A is positively correlated with Ki67 expression, suggesting that KIF20A may participate in the proliferation of gliomas.…”
Section: Discussionmentioning
confidence: 64%
“…KIF20A is a member of the KIF family, which has been reported to be upregulated in pancreatic cancer,29 breast cancer,14 and hepatocellular cancer 30. In the current study, we investigated the expression of KIF20A protein in gliomas using IHC and found that the expression of KIF20A is positively correlated with Ki67 expression, suggesting that KIF20A may participate in the proliferation of gliomas.…”
Section: Discussionmentioning
confidence: 64%
“…Knockdown of KIF20A could significantly inhibit the growth of HCC cells in vitro and also suppress the growth of HCC xenografts in vivo . Based on the survival data of 210 HCC patients from China, this study also showed elevated KIF20A expression was associated with poor survivals . Therefore, KIF20A might be a promising prognostic indicator in HCC.…”
Section: Introductionmentioning
confidence: 69%
“…6C). In addition, the protein degradation of Gli2 was accelerated significantly in Nek2A over-expressed HepG2 cells which is also a Hh-responsive cell line [30] (Fig. 6D).…”
Section: Nek2a Impairs Gli2 Activitymentioning
confidence: 88%